Confronting the Amazon's fire crisis: Evidence of early fire occurrence and increased atmospheric gases from the GOSAT satellite - de Souza Maria, Luciano [UNESP]; da Costa, Luis Miguel [UNESP]; Campos, Marcelo Odorizzi [UNESP]; Panosso, Alan Rodrigo [UNESP]; Basso, Luana Santamaria; da Silva, Carlos Antonio; La Scala, Newton [UNESP] (Elsevier, 2025)
Forest fires represent a significant threat to the Amazon biome, contributing to elevated greenhouse gases (GHGs) emissions. This study analyzes temporal trends in column-averaged concentrations of CO2 (XCO2) and CH4 (XCH4) in the atmosphere using satellite observations from GOSAT, while exploring the relationships between surface spectral indices and wildfire activity in the region. Key variables included the Enhanced Vegetation Index (EVI), Fire Radiative Power (FRP), and MODIS-based fire foci data. Additionally, Sun-Induced Fluorescence (SIF), XCH4, and XCO2 data were obtained from GOSAT for the period 2009–2019, alongside global forest fire emissions from the VIIRS-based Fire Emission Inventory (VFEI) for 2012–2019. Our findings indicate significant increases in monthly averages of XCO2 (>1.3 ppm) starting in April 2013, identified as a change point using the Pettitt test. Similarly, FRP values increased for April (>12 MW) and July (>23 MW), suggesting an earlier onset of wildfire activity and subsequent atmospheric impacts. These results align with VFEI emissions data, which also show rising GHG levels during the study period. The observed increases in wildfires and associated XCO2 concentrations are likely linked to anthropogenic activities, particularly land-use changes, underscoring the critical role of human influence in exacerbating GHGs emissions within the Amazon biome. These findings highlight the urgent need for sustainable land management strategies to mitigate the adverse impacts of wildfires and preserve the biome's role as a vital carbon sink.